2019
DOI: 10.1177/2192568219834894
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Multilevel Anterior Cervical Discectomy and Fusion Performed in an Inpatient Versus Outpatient Setting

Abstract: Study Design:Retrospective cohort study.Objective:To evaluate differences in patient factors, procedural factors, early outcomes and safety in mutlilevel anterior cervical discectomy and fusion (ACDF) in the inpatient versus outpatient setting.Methods:Patient demographics, operative factors, and outcomes of multilevel ACDF performed in an inpatient and outpatient setting were compared using Fisher’s exact test for categorical and Student’s t test for continuous variables.Results:Fifty-seven patients had surger… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
18
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(20 citation statements)
references
References 34 publications
(72 reference statements)
0
18
0
Order By: Relevance
“…Patients with significant comorbidities should undergo preoperative medical evaluation and optimization to assess their appropriateness as outpatient surgical candidates. Other common complications related to systemic effects such as nausea and urinary retention are identified early in PACU and can be managed as outpatients or admitted overnight, as needed 2…”
Section: Yesmentioning
confidence: 99%
See 1 more Smart Citation
“…Patients with significant comorbidities should undergo preoperative medical evaluation and optimization to assess their appropriateness as outpatient surgical candidates. Other common complications related to systemic effects such as nausea and urinary retention are identified early in PACU and can be managed as outpatients or admitted overnight, as needed 2…”
Section: Yesmentioning
confidence: 99%
“…Other common complications related to systemic effects such as nausea and urinary retention are identified early in PACU and can be managed as outpatients or admitted overnight, as needed. 2 The most immediate postoperative concern after ACDFs is potential airway compromise. An expanding postoperative retropharyngeal hematoma poses a catastrophic complication and serves as the predominant indication for a 23-hour observation admission.…”
mentioning
confidence: 99%
“…To this end, many studies have reported on the feasibility of ACDF, cervical arthroplasty, posterior cervical foraminotomy, and lumbar decompression in the outpatient setting. [2][3][4][5]15 Only in the past few years, however, can the same be said for lumbar fusions. In 2013 and 2014, the first 3 case series of outpatient transforaminal lumbar interbody fusions (TLIFs) were published.…”
Section: Outpatient Lumbar Fusionmentioning
confidence: 99%
“…1 Spinal decompression procedures and anterior cervical discectomy and fusions (ACDFs) are responsible for the majority of this trend, whereas lumbar fusions have lagged behind. [2][3][4][5] As a case in point, one study reported that the incidence of outpatient lumbar fusions was stagnant between 2008 and 2018. 6 In recent years, however, multiple studies have demonstrated favorable outcomes after outpatient lumbar fusion-particularly with the use of minimally invasive techniques.…”
Section: Introductionmentioning
confidence: 99%
“…Complication rates with ACDF are low enough that it can be performed even in an outpatient setting. 1,2 However, the surgery is not without risks and some can be devastating such as postoperative hematoma compression of the airway. [3][4][5][6][7] Some surgeons routinely place a suction drain to address postoperative hematoma.…”
mentioning
confidence: 99%